Working Conditions of Academics in the National System of Researchers at a Public University in the Mexican Southeast - Aquino Zuñiga, Silvia Patricia (2025)
The training of researchers and their insertion into the labor condition is an emerging issue that is gaining momentum among the scientific community. Training in postgraduate courses that belong to the National Postgraduate System (SNP) enables graduates to enter the National System of Researchers (SNII) given the demands and productivity developed during their training. The purpose of this paper focuses on the working conditions of female researchers belonging to the SNII at a public university in southeastern Mexico hired as hour-week-month (HSM). The objective of this paper is to present the working conditions of female research professors belonging to the SNII hired as HSM and the difficulties in obtaining a part-time or full-time position in a public university in southeastern Mexico. The work was carried out under a descriptive and exploratory research design, with a case study approach to six female professors-researchers from a Mexican public university. A questionnaire of 20 multiple-choice and open questions was applied. The categories of the instrument were sociodemographic data, activities carried out in the institution, challenges and obstacles to remain in the SNII. Based on the results, it is concluded that the employment status of HSM makes it difficult to maintain the distinction of SNII and that being part of the SNII does not guarantee professional development as researchers in the institution and obtaining a part-time or full-time contract due to the institutional policies for promoting academic staff.